Qur'an as Script: Dramatic Engagement and Spiritual Transformation in Sūrat Yūsuf - Bishr Pandikkad (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
This study examines Sūrat Yūsuf (Qur'an 12) as a divinely orchestrated dramatic narrative that transforms reading into participatory spiritual experience. Integrating Reader‑Response Criticism with Sayyid Qutb’s concept of al‑taṣwīr al‑fannī (artistic depiction), it demonstrates how dramatic form—dialogue, suspense, irony, and symbolic staging—facilitates the surah’s pedagogical and spiritual function. Using Aristotelian principles of catharsis, peripeteia (reversal), and anagnorisis (recognition), the paper argues that the surah’s aesthetics are inseparable from its revelatory purpose: to awaken moral consciousness through active engagement. Sūrat Yūsuf thus functions not merely as a sacred narrative but as a divine script performed within the believer’s consciousness—an ongoing enactment of revelation that unites aesthetic pleasure with spiritual transformation.